2014
DOI: 10.1007/s12639-014-0546-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of chitosan nanospheres on the immunogenicity of Toxoplasma lysate vaccine in mice

Abstract: Toxoplasmosis, a zoonotic parasitic disease, is a huge challenge for which there is no effective vaccine up till now. In this study, chitosan nanospheres encapsulated with Toxoplasma lysate vaccine was evaluated for its ability to protect mice against both acute and chronic toxoplasmosis models of infection. Results showed that chitosan nanospheres were equally effective to Freund's incomplete adjuvant (FIA) in enhancing the efficacy of Toxoplasma lysate vaccine. The effectiveness was demonstrated by the delay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 50 publications
(54 reference statements)
7
23
0
Order By: Relevance
“…However, N. sativa seeds essential oil was recently found to have antihelmenthic activity against S. mansoni infection (Mahmoud et al, 2002). Many studies used nanoparticles as vehicles to deliver drugs for the improvement of their therapeutic efficacy (El-Temsahy et al, 2016). In this study, we used chitosan as a drug carrier for N. sativa to improve its efficacy.…”
Section: Discssionmentioning
confidence: 99%
“…However, N. sativa seeds essential oil was recently found to have antihelmenthic activity against S. mansoni infection (Mahmoud et al, 2002). Many studies used nanoparticles as vehicles to deliver drugs for the improvement of their therapeutic efficacy (El-Temsahy et al, 2016). In this study, we used chitosan as a drug carrier for N. sativa to improve its efficacy.…”
Section: Discssionmentioning
confidence: 99%
“…Results of spleen tissue examination of infected control group (G2) showed the presence of tissue cysts in large numbers and pseudocysts of Toxoplasma. El Temsahy et al, [55] revealed the presence of Toxoplasma pseudocysts containing viable tachyzoites in spleen tissue of mice, using experimental infection by virulent RH strain. In SPF treated group (G3), spleen tissue showed decreased number of tissue cysts as compared to control group (G2), attributed to the synergistic effect of the drug (SPF) on nucleic acid synthesis in Toxoplasma.…”
Section: Discussionmentioning
confidence: 99%
“…Chitosan is a non-toxic, biodegradable, biocompatible natural polysaccharide and it was approved by the Food and Drug Administration (FDA) as a safe adjuvant and vaccine delivery system [150,151]. In addition, the chitosan formulation was able to improve the immunogenicity of a peptide-based vaccine and induced an immune response mediated by IgG2a [152].…”
Section: Development Of Pneumococcal Nanovaccinesmentioning
confidence: 99%